Hybrid Governance of Transboundary Commons: Insights from Southeast Asia. Issue 1 (2nd January 2020) - Miller, Michelle Ann; Middleton, Carl; Rigg, Jonathan; Taylor, David
Abstract : This article examines how hybrid environmental governance produces, maintains, and reconfigures common property across transboundary geographies of resource access, use, and ownership. Transboundary commons are a category of environmental goods that traverse jurisdictions and property regimes within as well as between nation-states. They are forged through collaborative partnerships between spatially dispersed state, private-sector, and societal institutions and actors. This article disaggregates these transboundary commoning arrangements into two geographically discrete yet conceptually intertwined categories of governance: mobile commons and in situ commons. We ground our enquiry in Southeast Asia, a resource-rich region where diverse formal and informal practices of resource organization blur the boundaries of environmental governance. Whereas environmental commons are often analyzed in terms of resource rights and entitlements, this article argues that a focus on power relations offers a more productive analytical lens through which to understand the dynamic and networked ways in which transboundary common property is continually being (re)made through processes of hybrid governance in response to changing ecological systems and shifting social realities. Key Words: ASEAN, common property, cross-border governance, environmental commons, hybrid governance.